Safety, tolerability, and pharmacokinetics of single and repeat ascending doses of CHF6001, a novel inhaled phosphodiesterase-4 inhibitor: two randomized trials in healthy volunteers - Mariotti, Fabrizia (Int J Chron Obstruct Pulmon Dis, 2018)
PURPOSE: The purpose of this study was to evaluate safety, tolerability, and pharmacokinetics (PK) of CHF6001, an inhaled phosphodiesterase-4 inhibitor. MATERIALS AND METHODS: Two healthy volunteer, randomized, double-blind, placebo-controlled studies were conducted. In each, Part 1 evaluated single ascending doses, with PK sampling up to 48 hours post-dose; Part 2 evaluated multiple ascending doses (Study 1, 7 days; Study 2, 14 days), with PK sampling up to 24 hours post-dose on first and last day of each period. In Study 1, treatments were administered via single-dose dry-powder inhaler (SDDPI; Aerolizer): Part 1, 20, 100, 200, 400, 800, 1,600, and 2,000 µg or placebo; Part 2, 100, 300, 600, 1,200, and 1,600 µg or placebo once daily (OD). In Study 2, treatments were administered via multi-dose dry-powder inhaler (MDDPI; NEXThaler): Part 1, 2,400, 4,000, and 4,800 µg or placebo; Part 2, 1,200, 2,000, or 2,400 µg twice daily (BID) or placebo. Modeling and simulation then compared OD and BID dosing via MDDPI. RESULTS: There was a clear correlation between CHF6001 dose and plasma concentration, following single and multiple doses and using SDDPI and MDDPI. CHF6001 plasma concentration area under the curve (AUC) was dose proportional, with steady state slopes of the fitted line of 0.95 (90% CI: 0.86, 1.04) for AUC0–24 h in Study 1, and 0.85 (90% CI: 0.38, 1.32) for AUC0–12 h in Study 2. Bioavailability waŝ30% higher with MDDPI than SDDPI. The PK simulation confirmed dose proportionality; the same total daily dose OD or BID via MDDPI resulted in similar 24 hours exposure, with BID dosing providing smaller fluctuation and lower maximum concentration. CHF6001 was well tolerated with no relationship between dose and adverse events. CONCLUSION: CHF6001 demonstrated a good safety profile. There was a clear dose proportionality for systemic exposure, with higher bioavailability via MDDPI, suggesting that the MDDPI provides better pulmonary drug deposition. BID dosing was associated with a better exposure profile.